PENGARUH CORPORATE GOVERNANCE DAN STRUKTUR KEPEMILIKAN TERHADAP KINERJA KEUANGAN (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2020-2022) - Firdaus, Faiq Fadhil; Dewayanto, Totok (Diponegoro Journal of Accounting, 2024)
This study aims to examine the influence of ownership structure and Corporate Governance on financial performance. The dependent variable in this study is financial performance as measured by Tobins'q and the independent variable in this study is Corporate Governance which is measured by board size which is the number of board of commissioners and directors, and board independence which affects financial performance activities while Ownership structure is measured using managerial and foreign ownership. The population in this study is mining companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. Sampling to collect data using the purposive sampling method. The sample used in this research was 180 companies with 60 companies per year for 3 years. The analysis test in this research uses multiple regression analysis. The research results show that board size has a positive effect on financial performance. Then, board independence has no effect on financial performance. Institutional ownership has a significant positive impact on financial performance.